Protection of SPF Chickens by H9N2 Y439 and G1 Lineage Vaccine against Homologous and Heterologous Viruses - Hyun-Kyu Cho; Yong-Myung Kang; Mingeun Sagong; Juhun Kim; Hyunjun Kim; Sungjun An; Youn-Jeong Lee; Hyun-Mi Kang (Vaccines, 2023)
Prior to the identification of low pathogenic avian influenza H9N2 viruses belonging to the Y280 lineage in 2020, Y439 lineage viruses had been circulating in the Republic of Korea since 1996. Here, we developed a whole inactivated vaccine (vac564) by multiple passage of Y439 lineage viruses and then evaluated immunogenicity and protective efficacy in specific-pathogen-free chickens. We found that LBM564 could be produced at high yield in eggs (108.4EID50/0.1 mL; 1024 hemagglutinin units) and was immunogenic (8.0 ± 1.2 log2) in chickens. The vaccine showed 100% inhibition of virus in the cecal tonsil with no viral shedding detected in either oropharyngeal or cloacal swabs after challenge with homologous virus. However, it did not induce effective protection against challenge with heterologous virus. An imported commercial G1 lineage vaccine inhibited viral replication against Y280 and Y439 lineage viruses in major tissues, although viral shedding in oropharyngeal and cloacal swabs was observed up until 5 dpi after exposure to both challenge viruses. These results suggest that a single vaccination with vac564 could elicit immune responses, showing it to be capable of protecting chickens against the Y439 lineage virus. Thus, our results suggest the need to prepare suitable vaccines for use against newly emerging and re-emerging H9N2 viruses.